UTILIZING THE GEOECO-BOOK LEARNING PACKAGE TO IMPROVE ECO-LITERACY OF Z GENERATION STUDENTS IN ELEMENTARY SCHOOLS - Erian Fatria; Agus Priadi; Guspri Devi Artanti; Syukra Alhamda (GeoEco, 2024)
The issue of environmental damage has become a contemporary issue and a limelight of the world today. To anticipate environmental disasters needed a strategy that can change the paradigm of the community so that people are more literate about the environment and have a high understanding of the importance of the environment. Environmental education exists and is designed to increase students' eco-literacy of environmental problems that occurred during the 21st century and provide efforts in saving the environment. This study aims to determine the geoeco-book learning package to improve the ecoliteracy of alpha generation of elementary school students. Research and Development was chosen by involving 50 students at Cipinang Melayu 04 East Jakarta Elementary School as a randomly selected sample. This geoeco-book learning package refers to the goal of environmental education which emphasizes the process of introducing values and environmental morals by explaining concepts relevant to basic ecological material in order to develop core competence eco-literacy. Data were analyzed using descriptive statistics and t-tests to verify product differences and effectiveness. The results showed that there was an increase in the effective and significant generation of Z generation of students after they learned the learning package. Therefore, even though they are an alpha generation, they have a serious interest in reading and understanding learning packages as products. This is one way to change eco-literacy and expect changes in their attitudes towards the environment that will ultimately be more positive in their environmental behavior.